Distribusi Ukuran Spasial-Temporal dan Berdasarkan Tingkat Kematangan Gonad Rajungan (Portunus pelagicus Linnaeus 1758) di Teluk Lasongko, Buton Tengah, Sulawesi Tenggara - Abdul Hamid; Yusli Wardiatno; Djamar T.F. Lumban Batu; Etty Riani (Fisheries and Marine Science Faculty - Jenderal Soedirman University, 2016)
The aim of the study was to reveal spatial-temporal distribution of the blue swimming crab(Portunus pelagicus Linnaeus 1758) in terms of size and gonad maturity stage of both male andfemale. Sampling of crab was conducted with a gill net from April 2013 until March 2014 inLasongko Bay. Of the whole population the mean size of male was smaller than that of females.Spatially smaller crabs (juveniles and young ones) inhabited mostly inner side of the bay, whilemedium size crabs occurred in the middle part of the bay. Big crabs were mostly found in theouter side of the bay. In terms of time, big sise of male and female crabs were collected inperiod of October to November and September to March, respectively. Small size of male andfemale occurred in February to September and in April, respectively. Related to gonad maturity,the sizes of both sexes with mature stages were variable. Ovigerous female (OF) was presencewidely in the bay, but the size of ovigerous females living in the shallow part of the bay wassmaller than those living in the deeper part. Keywords: blue swimming crab, size distribution, carapace width, spatial-temporal, gonadmaturity